Машины для рекультивации нарушенных земель: справочник - Надршин Т. К. Таиф Кутдусович; Гудошников С. И. Сергей Иванович; Новиков А. В. Александр Васильевич; Грачева З. И. Зоя Ивановна (Москва, Недра, 1981)
Авт. указаны на обороте тит. л.